Conventional papillary thyroid carcinoma: effects of cystic changes visible on ultrasonography on disease prognosis - Ja Young Kim; Eun-Kyung Kim; Hye Sun Lee; Jin Young Kwak (Ultrasonography, 2014)
Purpose To investigate the characteristics of papillary thyroid carcinoma (PTC) with cystic changes visible on ultrasonography (US). Methods This study included 553 PTCs in 553 patients between January 2003 and August 2004. One radiologist with 10 years of experience in thyroid imaging retrospectively reviewed the preoperative US images. Two different groups were formed according to two different reference points (group 1, 25%; group 2, 50%) of the cystic component. Patients between the groups were compared according to their clinicopathologic characteristics. Disease-free survival (DFS) was estimated. Cox’s multivariate proportional hazards regression model was used to identify the effect of variable factors on the recurrence risk. Results Fifty-six patients (10.1%) were confirmed to have tumor recurrence within the follow-up period. Thirty-five patients had regional metastasis, one had distant metastasis, eight had multiple site metastases, and 12 had biochemical recurrence. PTC patients with a ≤ 50% or PTC patients with a ≤ 25% cystic component did not have a statistically significant longer DFS than those with a >50% (hazard ratio [HR], 1.118; 95% confidence interval [CI], 0.255 to 4.910; P=0.883) or those with a >25% cystic component (HR, 0.569; 95% CI, 0.164 to 1.976; P=0.375), respectively. Moreover, independent predictors of recurrence were pathologic size, male gender, and lymph node metastasis, not a >50% or >25% cystic component. Conclusion The proportion of the cystic component in PTCs did not affect DFS.